CORRELATION OF IMPACTED MANDIBULAR THIRD MOLAR WITH INCIDENCE OF IPSILATERAL ANGLE AND CONDYLAR FRACTURES IN MANDIBULAR TRAUMA - Syed Yasir Ali Abidi; Adnan Babar; Kaleem Ullah Niazi; Ali Akhtar Khan; Atiqa Maryam; Nazish Rasheed (Pakistan Armed Forces Medical Journal, 2020)
Objective: This study aims to evaluate association of impacted lower third molars with incidence of ipsilateral mandibular angle and condylar fractures.